Induced production of a new dipeptide with a disulfide bridge by long-term fermentation of marine-derived Trichoderma cf. brevicompactum. Issue 51 (21st December 2016) - Yamazaki, Hiroyuki; Rotinsulu, Henki; Takahashi, Ohgi; Kirikoshi, Ryota; Namikoshi, Michio
Graphical abstract: Highlights: A new modified dipeptide was produced by long-term static fermentation of marine fungus. The structure of the new compound was determined by analyzing NMR and ECD spectra. The strain produced a bisabolane sesquiterpene by long-term agitating fermentation. Abstract: The marine-derived fungus Trichoderma sp. TPU199 (cf. T . brevicompactum ), originally isolated from a Palauan red alga, was found to produce unprecedented epipolythiodiketopiperazines, such as gliovirin and pretrichodermamide A. Long-term static fermentation of the strain induced the production of a new dipeptide, dithioaspergillazine A (1 ), together with aspergillazine A (2 ) and three anthraquinones (3 –5 ). The structure of1 was identified as a modified dipeptide possessing a disulfide bridge based on spectroscopic data for1 and comparisons with those for2 . On the other hand, long-term agitating fermentation of the strain led to the production of the known bisabolane-type sesquiterpene, (+)-12-hydroxysydonic acid (6 ), which formed the cyclic derivative7 during HPLC purification under acidic conditions. Compound1 exhibited cytotoxicity against HCT-15 and Jurkat cells with IC50 values of 13 and 1.3 μM, respectively. Compound2 did not affect the proliferation of these cancer cells up to a concentration of 22 μM.